Influence of carbohydrate intake on oxidative status among women with and without gestational diabetes mellitus - Garcia Alvarado, Jocelyn (2024)
Objective: To identify the influence of carbohydrate (CHO) intake on oxidative status among women with and without gestational diabetes mellitus (GDM). Materials and methods: A cross-sectional, observational and comparative study was carried out with two groups of 21 women each with and without GDM in the city of Toluca, Mexico, from January to December 2022. The sociodemographic parameters were determined by administering the patients a medical history questionnaire; anthropometric parameters such as body weight and height were measured; and biochemical parameters including total cholesterol (TC) and triglycerides (TG) were calculated. The oxidant/antioxidant status was assessed as follows: malondialdehyde (MDA) as oxidative stress marker; and catalase (CAT), superoxide dismutase (SOD) and total antioxidant capacity (TAC) as antioxidants. Dietary habits were evaluated through a 24-hour reminder in both groups of women to obtain the macronutrient classes, i.e., proteins, fats and CHOs. Based on the total carbohydrates (TCHOs), complex (CCHOs) and simple carbohydrates (SCHOs) such as sucrose were calculated. SCHOs per day were measured using the list of foods with sucrose content per 100 grams according to the Mexican Food Equivalence System (SMAE). The NutriKcal VO program was used for the dietary analysis. Statistical tests such as Student’s t test and Mann-Whitney U test were performed for the independent samples and nonhomogeneous variables, respectively, and Spearman’s rank correlation coefficient (p < 0.05) was determined using the IBM SPSS Statistics V19. Results: The results showed that the difference between the levels of TC (p < 0.029), TG (p < 0.029), enzymes CAT (p < 0.011) and SOD (p < 0.013), as well as MDA (p < 0.039) was significantly higher among patients in the group with GDM compared to that in the group without GDM. In addition, the group with GDM consumed a higher proportion of sucrose. Conclusions: Women with GDM have an imbalance in the oxidant/antioxidant status, influenced by the type of CHO they consume, particularly SCHOs such as sucrose.